SUSTAINABLE MANGROVE ECOTOURISM IN SURABAYA USING SWOT ANALYSIS - Abdul Halik (Fakultas Ekonomi Universitas 45 Surabaya, 2013)
Tourism is one of the key drivers of socio-economic development in a number of major countries and regions, especially in the city of Surabaya. Mangrove ecotourism is a traditional model of tourism that is undergoing transformation that raises some fact that tourism has the characteristics that are plants that can be made the syrups, taffy, etc. On the east coast of Surabaya the mangrove forest is a very attractive destination, because in addition to ecotourism there are collection egret birds that live there as a transit point as well as other animals such as monkeys. Newer classifications of tourism sector in Wonorejo consider include: beach tourism, domestic tourism, cultural tourism, rural tourism, camping tours, marine tours, cruises and city tours. The coordinates on the X-axis strength variable or = 0.754 and weakness variable or Y axis = 0.055. It means that sustainable mangrove ecotourism in Wonorejo are in a favorable situation because it has a pretty good chance and strength so that should be applied in these circumstances is the aggressive growth policy or aggressive strategies. Resolution of issues that need to be done include : (1) Sustainable mangrove ecotourism can generate local tax revenues to finance infrastructure improvements and quality of service (schools, NGO, park and recreation, roads, etc.). (2) Sustainable mangrove ecotourism can stimulate the development of local companies dedicated to this activity. (3) Social and cultural awareness which leads to the formation of larger socio-cultural association to preserve the diverse tourist. (4) Sustainable mangrove ecotourism can contribute to forest rehabilitation and conservation, animal and building conservation, and environmental improvement. (5) The siding of Surabaya government in developing mangrove ecotourism to be more recognized by the public both inside and outside the country. Relying on technology to create sustainable rural tourism offering travelers up to their potential and increase the opportunity to enjoy the beauty of the beach and the sun. Coordination and planning of all initiatives in tourism, undertake the new threats and vulnerabilities emerge, encourage environmental sustainability and products competitive that meet the needs of more experienced people as well as all aimed at improving the current situation, not only economically but also socially.